Peningkatan Kesiapsiagaan Masyarakat dalam Menghadapi Pandemi Covid 19 di Kelurahan Kotabaru Kota Yogyakarta - Ika Afianita Suherningtyas; Sola Tri Astuti; Eva Kurnia Setyawati; Laela Nurul Istiqomah; Zulham Huzaeni (Jurnal Pengabdian Pada Masyarakat, 2021)
INCREASED COMMUNITY PREPAREDNESS IN FACING THE COVID 19 PANDEMIC IN KOTABARU URBAN VILLAGE, YOGYAKARTA CITY. Coronavirus Disease 2019 (Covid-19) is a disease that is transmitted between humans through droplets caused by the corona virus, attacks the respiratory tract so that it can cause high fever, cough, flu, shortness of breath and sore throat and even death. The number of covid-19 cases has always increased every day to become a world problem, including the Kotabaru Yogyakarta City. This area has high socio-economic activities that involve direct physical contact. This study aims to improve community preparedness in RT 16 RW 04, Krasak Village, Kotabaru Village, Yogyakarta City in the face of the Covid-19 pandemic. Public knowledge about Covid-19 is an important asset in prevention efforts to minimize transmission by taking precautions at the individual and community levels, implementing health protocols, and promotional media. The research method used a qualitative descriptive analysis of the phenomenon of the study subject and the purposive sampling method for determining correspondence. The research instrument used a questionnaire containing several questions about covid-19 knowledge. The parameters listed are public knowledge about Covid-19 and its origins, characteristics, how to protect themselves, prevention, and access to information. The results of the study of 34 respondents showed that 26% had low knowledge, 59% had moderate knowledge, and 15% had high knowledge regarding covid-19. Community empowerment activities carried out include dissemination of information on covid-19, implementing PHBS (Clean and Healthy Lifestyle) behavior, forming a Covid-19 task force at the RT level, forming a food barn, and providing assistance in the form of funds and goods, and food for residents who carry out self-quarantine.